Diminishing Role of the Youth and Civil Society Organizations in the Process of PeaceBuilding in Central Equatoria State and beyond - Wani, Chaplain Kenyi (Ethiopian Journal of Social Sciences, 2022)
AbstractThe youth and civil society organizations have important roles to play in the process of peacebuilding, but they have not been fully engaged in South Sudan. Their role in the nine functions to help prevent reoccurrence of conflict was neglected. This study investigated the reason why such negligence occurred. The youth became vulnerable to recruitment to fight for politicians to gain recognition for position in the national government, making conflicts sources of employment. Civil society organizations, which should have been responsible for the signing of legitimate contracts with the national government and the business sector, and as an intermediary between the government and the society, were weak to negotiate effective social contracts. Stratified purposive interviews were conducted in Juba and Kajokeji counties, including two focus group discussions. Workshops were attended to fill in information gaps from the other states. Primary data was gathered through in-depth interviews with key informants: civil society organizations, national and international non-governmental organizations, government officials, and former fighters. Secondary sources were gathered from the University of Juba. The data was analyzed using the process of ethnography and discourse analysis, interpretation and observation. The findings of the study show that the national government adopted a centralized system of administration, and youth and civil society organizations did not play an effective role in preventing the reoccurrence of conflicts. Practices of good governance became difficult to establish a democratic state, leading to neglect of the role of the youth and civil society organizations in the process of peace-building, Inclusivity, good policies and appropriate conditions for further research would be needed.